Conjugate heat transfer analysis of PCM suspensions in a circular pipe subjected to external cooling convection: Parameter effects. (December 2020) - Ho, C.J.; Wang, Z.C.; Chen, R.H.; Lai, Chi-Ming
Highlights: Conjugate heat transfer of PCM suspensions in a circular pipe was numerically investigated. The circular pipe is confined to external cooling convection. PCM concentration, bio and ste affected the overall thermal performance. Pe only had a significant effect on the axial heat transfer of the wall. Abstract: In this paper, a numerical method was used to investigate the conjugate heat transfer of phase change material (PCM) suspensions in a circular pipe under external cooling convection. The parameters considered in this study and their ranges were the volumetric fraction of PCM particles ( cv ) = 0–0.2, the Biot number ( Bio ) = 0.1–100, the Stefan number ( Ste ) = 0.01–0.2, and the Peclet number ( Pe ) = 100–1000. The results showed that the PCM concentration, Bio, and Ste had significant effects on the fluid temperature, inner/outer wall temperature, and inner/outer wall heat flux, while Pe only had a significant effect on the axial heat transfer of the wall. When a PCM-containing working fluid was used for cooling, the PCM latent heat could directly affect the fluid outlet temperature and the cooling effect. If the latent heat is changed, other thermal system parameters should be adjusted accordingly.